Gernika, 1937 : The Market Day Massacre - Irujo Ametzaga, Xabier (Book collections on Project MUSE., 2015)
On April 26, 1937, a massive aerial attack by German and Italian forces reduced the Basque city of Gernika to rubble and left more than sixteen hundred people dead. Although the assault was initiated as part of a terror bombing campaign by Francoists against Basque Republican forces during the Spanish Civil War, its main intent was to test the effectiveness of the rising German Luftwaffe's new equipment and strategies. To produce this detailed analysis of the political and military background of the attack and its subsequent international impact, Xabier Irujo examined archives and official government documents in several countries and conducted numerous interviews with Basques who survived. His account of the assault itself, based on eyewitness reports from both victims and attackers, vividly recalls the horror of that first example of the blitz bombing that served the Germans during the first years of World War II. He reveals the US and British governments' reaction to the bombing and also discusses efforts to prosecute the perpetrators for war crimes. Irujo relates the ways in which the massacre has been remembered and commemorated in Gernika and throughout the worldwide Basque diaspora.--